Investor behavioral intention in investment-based crowdfunding: a systematic literature review - Astiwi Indriani,; Aisyah Abdul Rahman,; Shifa Mohd Nor,; Nur Sa’adah Muhamad, (Penerbit Universiti Kebangsaan Malaysia, 2024)
The study presents a comprehensive systematic review to deepen our understanding of the factors that guide investment intentions within the crowdfunding sector, with a specific focus on equity-based and lending-based platforms. Using the Reporting Standards for Systematic Evidence Synthesis (ROSES) approach, articles were sourced from the WOS and Scopus databases. Our analysis revealed eight main themes influencing investor intention: investor-based factors, fundraiser-based factors, platform-based factors, project-based factors, trust, motivation, risk, and value. Notably, trust emerged as an essential factor influencing investor intention in investment-based crowdfunding, not only as a direct predictor but also as a mediator that connects other variables to behavioral intention. This study’s broad-reaching implications extend to investors, crowdfunding platforms, borrowers, government policymakers, and researchers. By establishing an insightful foundation for future research and providing actionable insights for practitioners seeking to foster trust, manage risk, and harness both intrinsic and extrinsic motivations, our findings bear the potential to shape the evolution of investment-based crowdfunding in the coming years.